Allergic contact dermatitis caused by nail acrylates in Europe: an EECDRG study - Gonçalo, Margarida; Diepgen, Thomas L. (Contact dermatitis, 2018)
Background Allergic contact dermatitis (ACD) caused by nail acrylates, also including methacrylates and cyanoacrylates here, is being increasingly reported. Methods A retrospective study in 11 European Environmental Contact Dermatitis Research Group (EECDRG) clinics collected information on cases of ACD caused by nail acrylates diagnosed by aimed testing between 2013 and 2015. Results Among 18 228 studied patients, 136 had ACD caused by nail acrylates (0.75%; 95%CI: 0.60-0.90), representing 67.3% (95%CI: 60.4-73.7) of ACD cases caused by acrylates. There were 135 females and 1 male, with a mean age ± standard deviation of 36.7 ± 12.2 years; 59 (43.4%) were exposed as consumers, and 77 (56.6%) were occupationally exposed. Occupational cases were more frequent in southern Europe (83.7%), and were younger (mean age of 33.4 ± 8.9 years); most developed ACD during the first year at work (65.0%), and at least 11.7% had to leave their jobs. Skin lesions involved the hands in 121 patients (88.9%) and the face in 50 (36.8%), with the face being the only affected site in 14 (10.3%). Most patients reacted to two or more acrylates on patch testing, mainly to 2-hydroxyethyl methacrylate (HEMA) (92.5%), 2-hydroxypropyl methacrylate (88.6%), ethylene glycol dimethacrylate (69.2%), and ethyl cyanoacrylate (9.9%). Conclusions Nail cosmetics were responsible for the majority of ACD cases caused by acrylates, affecting nail beauticians and consumers, and therefore calling for stricter regulation and preventive measures. As HEMA detects most cases, and isolated facial lesions may be overlooked, inclusion of this allergen in the baseline series may be warranted.
First published: 21 December 2017
Gesehen am 25.10.2018